Estratégias de Licitação de Produtores Renováveis no Mercado Ibérico de Eletricidade - José Gabriel Teixeira Pinto Xavier de Oliveira (2020)
The energy sector has undergone major changes, particularly in Portugal. Currently, there is complete liberalization of the electricity sector. This allows any customer choose their energy supplier, regardless of the customer's contracted power. Thus, like other European countries, a market agent has been created in the design of facilitating trade relations between producer and trader (trading agent). This trading agent, in a market environment, is known as an aggregator. This agent aims to minimize the costs to the trader and maximizes the profits of producers. The aggregator will have to know the energy profile and the risk associated with each producer, calculating the forecast resulting from its participation in the Iberian Market and will have to find the bidding strategies in the market (daily, intraday and intraday continuous) which result in the minimization of deviations between forecasts and real productions and thus, the associated costs of these deviations In this dissertation, five renewable power plants, who are contractually linked with the company Energia Simples are analyzed with the aim to verify the profitability of these contracts for both parties. In this framework, an analysis is made based on the differences between renewable production and the programme (forecast) from which it is perceived that sometimes these deviations are too high and result in higher costs. Consequently, the greater the deviations, the greater the expenses and, therefore, the lower the profit of each party. Thus, bidding strategies which result in the reduction of these differences are sought. The bidding strategies put in place involve the different markets (daily, intraday and continuous intraday) in the search for the ideal solution that results in higher profits for both parties.